Continuous Wave (CW) and Micropulse Transscleral Laser Cyclophotocoagulation (TLC) for Refractory Glaucoma in African Eyes: A Comparative Study - Olufemi Oderinlo; Adunola Ogunro; Adekunle Hassan; Abiola Oladeji; Oyekunle Idris (Medical Science: Trends and Innovations Vol. 8, 2025)
Background: Transscleral laser cyclophotocoagulation (TLC) has shown promising results in the treatment of refractory glaucoma and practically replaced cyclocryotherapy due to better outcomes, efficacy, increased safety, and tolerability. Two protocols of TLC have gained more popularity as effective modalities, TLC with the semiconductor diode laser and TLC with the Nd: YAG laser. Aims: The aim of the study is to report the efficacy of transscleral diode laser photocoagulation and compare outcomes between the continuous wave (CW) and micropulse wave (MP) protocols for refractory glaucoma in African eyes. Methods: A non-randomized prospective comparative study of patients who had transscleral diode laser photocoagulation for refractory glaucoma between January 2021 and December 2021in Eye Foundation Hospital Lagos, Nigeria was done. Results: A total of 52 eyes of 52 patients were analyzed. The mean age of patients was 66 ± 12.5 years. The mean preoperative intraocular pressure (IOP) was 31.2 ± 11.9 mmHg. Overall post-operative mean IOP was 17.9 ± 8.6 mmHg at 4 weeks, 21.0 ± 9.9 mmHg at 8 weeks and 20.6 ± 11.4 mmHg at 12 weeks. The difference between mean preoperative and postoperative IOP measured at week 12 was statistically significant (p<0.001). Both continuous wave and micropulse wave protocols were effective at reducing intraocular pressures, the micropulse group had a mean difference between preoperative IOP and postoperative IOP at week 12 of 7.5 ± 6.7 mmHg (p=0.001), while the continuous wave laser group had a mean difference of 11.7 ± 13.7 mmHg (p<0.001). The micropulse group achieved a higher percentage of success in 11 eyes (78.6%) compared with 24 eyes (63.2%) in the continuous wave group. This difference was not statistically significant (p=0.341). Conclusion: Both the continuous wave (CW) and micropulse wave (MP) protocols of transscleral diode laser photocoagulation were found effective at significantly reducing IOP in our study of African eyes with refractory glaucoma. Although the MP group achieved a higher percentage of absolute success, this was not statistically significant.